Gaya Kepemimpinan Kepala Pepustakaan Institut Agama Islam Negeri Langsa Berdasarkan Emotional Intellegience - Fahrun Nisak Al-Husna (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Leaders are the main key to management, meaning that management goals will be achieved if they have a leader who is firm, wise and professional. The emotional intelligence of a leader plays an important role in an organization and the people who work in it, especially in the library where information is managed. The purpose of this article is to determine the leadership style in dealing with the globalization of information in the Langsa State Islamic Institute library based on emotional intelligence. This article is a qualitative descriptive article with data collection techniques using observation, interviews and literature study. Based on the results of the study, it is known that the leadership at the Langsa State Islamic Institute Library has made the library develop very well in overcoming the globalization of information for the user community, both students, academics and the general public. This is done by the head of the library. Under his leadership, the librarian of the Langsa State Islamic Institute of Religion has implemented a leadership style based on emotional intelligence that includes visionary, mentoring, affiliative, democratic, pacesetter, and governing in today's era of information globalization. A good leadership style based on emotional intelligence is needed in libraries, especially in the face of globalization of information as it is now.